A viscous damping model for piston mode resonance. (25th July 2019) - Tan, L.; Lu, L.; Tang, G.-Q.; Cheng, L.; Chen, X.-B.
Abstract : A viscous damping model is proposed based on a simplified equation of fluid motion in a moonpool or the narrow gap formed by two fixed boxes. The model takes into account the damping induced by both flow separation and wall friction through two damping coefficients, namely, the local and friction loss coefficients. The local loss coefficient is determined through specifically designed physical model tests in this work, and the friction loss coefficient is estimated through an empirical formula found in the literature. The viscous damping model is implemented in the dynamic free-surface boundary condition in the gap of a modified potential flow model. The modified potential flow model is then applied to simulate the wave-induced fluid responses in a narrow gap formed by two fixed boxes and in a moonpool for which experimental data are available. The modified potential flow model with the proposed viscous damping model works well in capturing both the resonant amplitude and frequency under a wide range of damping conditions.